France : 2006 Article IV Consultation-Staff Report, Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2006)
France's economic short-term outlook is positive, and long-term prospects have improved. Fiscal adjustment remains high on the government's agenda. Tax reforms have improved the economy's growth potential. Reforms in financial, labor, and product markets are necessary to boost job creation, prepare the economy for aging, and allow it to benefit from global activity. The financial sector's profitability and capitalization put it in a good position to manage increasing risks. Structural reforms in labor and product markets remain essential to boost long-term growth and secure fiscal sustainability.